Knitting patterns of biodiversity, range size and body size in aquatic beetle faunas: significant relationships but slightly divergent drivers. (4th January 2019) - Heino, Jani; Alahuhta, Janne
Abstract : 1. Ecogeographical rules refer to recurring patterns in nature, including the latitudinal diversity gradient (LDG), Rapoport's rule and Bergmann's rule, amongst others. In the present study, the existence of these rules was examined for diving beetles (Coleoptera: Dytiscidae), a family of aquatic predatory beetles. 2. Assemblage‐level data were analysed for diving beetles, focusing on species richness, local contribution to beta diversity (LCBD), mean range size and mean body size across the biogeographical provinces of Northern Europe. First, each of these variables was correlated with latitude, and then variation in each variable was modelled using actual environmental variables in boosted regression tree analysis. 3. Species richness was found to decrease with latitude, LCBD increased with latitude, mean range size did not show a significant relationship with latitude, and mean body size decreased with latitude. The latter finding was in contrast to Bergmann's rule. The actual environmental variables best predicting variation in these four response variables varied among the models, although they generally included temperature‐related and land use variables as the most influential ones. 4. The results obtained in the present study suggest that diving beetles conformed to the LDG, did not follow Rapoport's rule, and showed a reversed latitudinal gradient in the context of Bergmann's rule. In addition, species‐poor provinces harboured ecologically most unique faunas, suggesting that species richness and LCBD are complementary measures of biodiversity. 5. Even though general support was not found for most of the ecogeographical rules examined, the findings of the present study are interesting because they suggest that aquatic ectothermic invertebrates may show patterns different from those originally described for terrestrial endothermic vertebrates. Abstract : Diving beetles conform to the latitudinal diversity gradient. They do not follow Rapoport's rule. The beetles showed a reversed gradient in the context of Bergmann's rule.